Values‐Based Measures of Impacts to Indigenous Health. Issue 8 (2nd December 2015) - Gregory, Robin; Easterling, Doug; Kaechele, Nicole; Trousdale, William
Abstract : Values‐based indicators of risks to Indigenous health have the potential to improve the accuracy and quality of a wide range of decisions affecting Native lands and cultures. Current health impact assessment approaches often omit important health priorities rooted in the history, social structures, and cultural context of Indigenous communities. Insights and methods from the decision sciences can be used to develop more culturally appropriate and context‐relevant health indicators that can articulate and track changes to important dimensions of Indigenous health. Identifying and addressing priority cultural, social, economic, and environmental contributors to the health of Indigenous communities will help to generate better project alternatives and foster more responsive choices.